SANKSI PIDANA TERHADAP PELAKU PEMBANTU KEJAHATAN TERHADAP NYAWA - Agus Vijayantera, I Wayan; Purwanti, Ni Putu (Kertha Wicara : Journal Ilmu Hukum; Vol. 01, No. 03, Juli 2013)
Murder is a brutal crime because the purpose of murderer is to take someone else life. when commit the murder sometimes there are people who help implement crime (accomplice). As accomplice has different role during the commission of a crime, they will be punished in different way. The problem is how to decide which penalties to give as this is a murder case. The purpose of this study is to know which penalties should be applied for accomplice of attempted murder as regulated in the Criminal Code (KUHP). The method used to analyze the problem is the normative law method. Accomplice is described in article 56 of the Criminal Code. The penalties for accomplice are regulated in article 57 of the Criminal Code. Based on those articles, the penalties for accomplice of attempted murder is jail punishment for certain time.
Keywords: Murder, Life, Crime, Accomplice